The power of AI: enhancing customer loyalty through satisfaction and efficiency - Pragya Singh; Vandana Singh (Cogent Business & Management, 2024)
In the rapidly evolving landscape of customer service, integrating AI-powered solutionshas emerged as a game-changer. This study delves into the intricate dynamics of AI-Powered Customer Service and its profound impact on customer loyalty, specifically focusing on the mediating roles played by customer satisfaction and perceived efficiency. Data were collected from 373 respondents in a cross-sectional study conducted in 2023. A structured questionnaire was administered electronically to individuals with recent experiences with AI-powered customer service within the last six months. The findings provide compelling evidence of the significant influence of AI-Powered Customer Service on customer satisfaction and perceived efficiency, as indicated by path coefficients of 0.91 and 0.95, respectively. Moreover, a strong relationship between customer satisfaction and loyalty (path coefficient = 1.05) and perceived efficiency and customer loyalty (path coefficient = 0.22) underscores their pivotal roles in driving customer loyalty. Organizations should strategically embrace AI-powered customer service, emphasizing efficiency and customer satisfaction. They prioritize customer-centric design in AI solutions to align technology with customer preferences and needs.
Keywords: 650; Customer Service; Customer Loyalty; Customer Satisfaction; Perceived Efficiency; Customer Experience; AI Powered customer service